A New Resistance Gene against Potato Late Blight Originating from Solanum pinnatisectum Located on Potato Chromosome 7 - Yang, Le; Wang, Dongdong; Xu, Yong; Zhao, Hua; Wang, Lei; Cao, Xiaoli; Chen, Yue; Chen, Qin (Frontiers in Plant Science, 2017)
Late blight, caused by the pathogen Phytophthora infestans, is one of the most devastating diseases of potato. Here, we describe a new single dominant resistance gene, Rpi2, from the Mexican diploid wild species Solanum pinnatisectum that confers high level and broad spectrum resistance to late blight. The Rpi2 locus confers full resistance to complex isolates of P. infestans, for which race specificity has not yet been demonstrated. This new gene, flanked by the RFLP-derived marker SpT1756 and AFLP-derived marker SpAFLP2 with a minimal genetic distance of 0.8 cM, was mapped to potato chromosome 7. Using the genomic sequence data of potato, we estimated that the physical distance of the nearest marker to the resistance gene was about 27 kb. The map location and other evidence indicated that this resistance locus was different from the previously reported resistance locus Rpi1 on the same chromosome from S. pinnatisectum. The presence of other reported resistance genes in the target region, such as Gro1-4, I-3, and three NBS-LLR like genes, on a homologous tomato genome segment indicates the Rpi2-related region is a hotspot for resistance genes. Comparative sequence analysis showed that the order of nine markers mapped to the Rpi2 genetic map was highly conserved on tomato chromosome 7; however, some rearrangements were observed in the potato genome sequence. Additional markers and potential resistance genes will promote accurate location of the site of Rpi2 and help breeders to introduce this resistance gene into different cultivars by marker-aided selection.